Penggunaan Basis Salep Ekstrak Etanolik Biji Mahkota Dewa (Phaleria macrocarpa ) Sebagai Anti Bakteri Terhadap Staphylococcus aureus ATCC 25923 - Rika Widyapranata (Fakultas Farmasi Universitas Setia Budi, 2011)
Mahkota dewa (Phaleria macrocarpa (Scheff) Boerl) belongs to the family of Thymelaeaceae, the seed contains flavonoid, tannin and alkaloid. Extraction was carried out by means of a soxhlet. The objectives of this experiment were to study the antibacterial activity of mahkota dewa seed extract, to select the best ointment base and the effective concentration of the seed extract of the ointment. Antibacterial activity of the ethanolic seed extract of mahkota dewa was tested by diffusion method and formulated into hydrocarbon, absorption, emulsion and water soluble ointment base each containing 3% of the seed extract to determine the best ointment base. Ointment with water soluble base (the best among above mentioned ointment base) with an extract concentration of 2%, 3%, 4% and 5% were made and applied to the infected area twice daily and observations made until the wound has dried. Topical ointment with 1% Gentamycin was used as positive control. Result of the experiment showed that ethanolic seed extract of mahkota dewa and the ointments with the above mentioned four concentrations have an antibacterial activity against Staphylococcus aureus ATCC 25923 indicated by the disappearance of the pus and healing of the wound. Ointment of water soluble base with 4% seed extract of mahkota dewa has the most effective antibacterial property.